2017
DOI: 10.5547/01956574.38.4.lgro
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in Energy Intensity in the EU-28: Evidence from a New Decomposition Method

Abstract: A number of measures have been adopted in order to achieve a better use of energy involving renovations of buildings, electronic appliances and heating facilities, installation of smart meters for electricity and gas. Besides these measures, EU member countries are required to prepare a National Energy Efficiency Action Plan every three years (European Parliament and the Council of the EU, 2006).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…As mentioned earlier, many research has been employed traditional inequality measures to investigate the distributions of energy economic indicators (Grossi and Mussini, 2017;Lawrence et al, 2013;Duro et al, 2010, Ezcurra, 2007Sun, 2002). One of the main features of these indexes is that every measure set different weights to the variable distribution, thus in some cases the yield may potentially differs over time (Duro, 2012).…”
Section: Methodology and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned earlier, many research has been employed traditional inequality measures to investigate the distributions of energy economic indicators (Grossi and Mussini, 2017;Lawrence et al, 2013;Duro et al, 2010, Ezcurra, 2007Sun, 2002). One of the main features of these indexes is that every measure set different weights to the variable distribution, thus in some cases the yield may potentially differs over time (Duro, 2012).…”
Section: Methodology and Datamentioning
confidence: 99%
“…The dynamics of energy intensity of GDP can be very varied across countries and period of time (Roca and Alcántara, 2002;Alcantara and Duro, 2004). Some research has been done to examine the inequalities of energy usage evolution and economic indicators differences (Grossi and Mussini, 2017;Sáez-Pascual et al, 2017;Lawrence et al, 2013;Duro et al, 2010;Sun, 2002). Those studies showed that the dynamics of energy intensity might reflect the differences in the economic structure and technologies level in a country.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we use the Zenga inequality index to comprehensively measure the extent of interregional disparities. Based on the upper and lower arithmetic means of each point of the distribution, one of the main advantages of the Zenga index is that it can be used to reveal the contribution of each observation sample to the overall disparities (Grossi & Mussini, 2017; Wang et al, 2020). Moreover, this paper combines the Zenga index with the index decomposition analysis method proposed by Ang (2004) and Wang and Zhou (2018) and proposes a novel and systematic method to decompose the Zenga index into multiple multiplicative and additive contributors.…”
Section: Introductionmentioning
confidence: 99%
“…The first efforts were concentrated on the decomposition of energy consumption by using the Index Decomposition Analysis (IDA) (e.g. Ang and Zhang, 2000;Fisher-Vanden et al, 2004;Grossi and Mussini, 2017;Croner and Frankovic, 2018) while others utilized the index of energy intensity (EI) which is defined as the amount of energy used per unit of output-activity. Nevertheless, as Shorrocks (2013) pointed out, the deficiencies of the above-mentioned measures led to the introduction of more complex parametric and nonparametric models in literature.…”
Section: Review Of Literaturementioning
confidence: 99%